2021
DOI: 10.3390/ijerph19010115
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Cohabitants of Patients Suffering Inflammatory Bowel Disease: A Cross-Sectional Study

Abstract: (1) Background: Inflammatory bowel disease (IBD) is a chronic inflammatory condition with a significant impact on patients’ general health perception. No studies have considered consequences of IBD on cohabitants. (2) Aims: The aims of this study were to address the influence of IBD on cohabitants’ quality of life (QoL) and the factors potentially conditioning this impact. (3) Methods: We conducted a cross-sectional study in which IBD patients and their cohabitants were invited to participate. Validated questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…There are several factors that can contribute to the impact of a disease on those living with the patients. First of all, worse disease control has been associated with poorer quality of life among cohabitants in a variety of medical conditions, such as inflammatory bowel disease [ 31 ], psoriasis [ 16 ] and hidradenitis suppurativa [ 17 ]. On the other hand, the diseases themselves can cause alterations in the mood and personality traits of the patients [ 5 , 18 , 32 ], which could favor the negative impact on the social network close to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that can contribute to the impact of a disease on those living with the patients. First of all, worse disease control has been associated with poorer quality of life among cohabitants in a variety of medical conditions, such as inflammatory bowel disease [ 31 ], psoriasis [ 16 ] and hidradenitis suppurativa [ 17 ]. On the other hand, the diseases themselves can cause alterations in the mood and personality traits of the patients [ 5 , 18 , 32 ], which could favor the negative impact on the social network close to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the issue of the quality of life of cohabitants of patients suffering from chronic diseases, such as inflammatory bowel disease [ 24 ], psoriasis [ 11 ], chronic spontaneous urticaria [ 25 ], or hidradenitis suppurativa [ 12 ]. In this line, there are many factors that could be responsible for this negative impact.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study shows how anxiety and depression in patients is associated with a negative impact on cohabitants in terms of a poorer quality of life, and higher rates of anxiety and depression. To the best of our knowledge, already available scientific literature for other chronic diseases have not addressed this issue [ 12 , 24 ]. Social and psychological support for patients would probably improve their mood status disturbances, therefore resulting in a better quality of life for cohabitants, as well as lower rates of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs) comprise two main diseases ulcerative colitis (CU) and Crohn's disease (CD), which can cause gastrointestinal and systemic symptoms usually characterized by alternating periods of relapses and remissions 1,2 . Previous studies have shown a distinct decrease both in a patient's and their family members' overall quality of life (QoL) 3–5 . The inflammatory bowel disease (IBDQ) score has been found to be a good tool for assessing the negative impact on several aspects of patients' everyday life 6 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Previous studies have shown a distinct decrease both in a patient's and their family members' overall quality of life (QoL). [3][4][5] The inflammatory bowel disease (IBDQ) score has been found to be a good tool for assessing the negative impact on several aspects of patients' everyday life. 6 No previous studies that separately addressed the possible adverse effects of IBD on household chores were found by our study group.…”
Section: Introductionmentioning
confidence: 99%